An exploratory study on the adoption of collateral in Muamalat practices / Nurul Hani Hasbi. - Hasbi, Nurul Hani (2019)
Nowadays, muamalat practices have been widely used in Malaysia also all around the world. One of the practical uses of muamalat is ar-Rahn or collateral. Ar-Rahn is one of the securities used to get something or goods on the collateral. In this study, the author has set several objectives which are are to explain the concept of collateral, discussing the scholar’s opinions on the difference in meaning between ar-Rahn and collateral and also the related contracts in collateral. The study found that collateral is transaction that practice by Islamic banking to provide financing towards consumers. The practice of collateral is contrary to the conventional bank’s financing products. This is because the keeping-fee of the both collateral in Islamic and conventional are different. In fact, collateral do not charge high wages, while conventional charges are high and also include interest-fees which containing riba. Majority scholars permit the practice of collateral based on their ijtihad to provide maslahah among the society. There is a problem regarding the use of collateral in Islamic banking and financing due to the meaning of ar-Rahn and collateral itself. Lastly, there are many adoption that have been used in mumalat practices such as in financing and pawnbroking.